2016
DOI: 10.1590/s0102-05362016003013
|View full text |Cite
|
Sign up to set email alerts
|

Selection of tomato genotypes for processing with high zingiberene content, resistant to pests

Abstract: Tomato cultivars resistant to arthropod pests are an important tool to reduce the use of pesticides. Resistance sources can be found in wild Solanum species such as S. habrochaites, which shows high levels of zingiberene (ZGB). This study aimed to evaluate the resistance of a tomato F2 progeny to spider mite and whitefly by evaluating the ZGB content, in laboratory, in plants from the F2 population of the interspecific crossing Solanum lycopersicum cultivar Redenção x Solanum habrochaites var. hirsutum (PI-127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In comparison with other previously studied rhizomes cultivated in different areas of the world, Japanese samples of Zingiber officinale may be perceived as rich sources of zingiberene—a strong pesticide [25], geranial—an anti-inflammatory agent [26], and ( E , E )-α-farnesene, known for its antibacterial and antifungal properties [27]. …”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other previously studied rhizomes cultivated in different areas of the world, Japanese samples of Zingiber officinale may be perceived as rich sources of zingiberene—a strong pesticide [25], geranial—an anti-inflammatory agent [26], and ( E , E )-α-farnesene, known for its antibacterial and antifungal properties [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Redenção and RVTZ-09 (low ZGB content) were the most preferred genotypes by T. urticae . Lima et al (2016) evaluating these same ZGB-rich genotypes observed a strong repellency effect against T. urticae and whitefly Bemisia tabaci (Genn.). The results indicated that non-preference is a mechanism by which ZGB-rich genotypes express resistance to the two-spotted spider mite.…”
Section: Discussionmentioning
confidence: 90%
“…Plants that produce and release chemical compounds (allelochemicals) affecting arthropod behavior and biology, may express resistance through both antixenosis (non-preference) and/or antibiosis ( War et al, 2012 ). In tomato, resistance has been extensively reported in the literature as mediated by different allelochemicals against arthropod pests such as mites ( Gonçalves et al, 2006 ; Resende et al, 2008 ; Lucini et al, 2015 ; Lima et al, 2016 ), whiteflies ( Freitas et al, 2002 ; Silva et al, 2009 ; Lima et al, 2016 ), and lepidopterans ( Maluf et al, 2010 ; Dias et al, 2013 ; Lima et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zingiberene, the chief component of the Z. officinale essential oil here analyzed, is a monocyclic sesquiterpene hydrocarbon with natural antioxidant and cytotoxic activities: it is capable of protecting against H 2 O 2 -induced cytotoxicity and oxidative DNA damage in neuronal cells [35] as well as inhibiting the growth of lymphocytic cells in a dose-dependent manner [36]. Furthermore, high zingiberene content in tomato plants provides resistance against arthropod pests including spider mite ( Tetranychus urticae ) and whitefly ( Bemisia tabaci ) [37,38]. On the other hand, β-sesquiphelladrene, the main isomer of zingiberene and second main compound in the ginger essential oil here analyzed, has antiviral and antifertility effects [38] as well as anticancer potential by inducing apoptosis through mitochondrial pathways [39].…”
Section: Resultsmentioning
confidence: 99%